Relaxation for Critically ill Patient Outcomes and Stress-coping Enhancement (REPOSE): a protocol for a pilot randomised trial of an integrative intervention to improve critically ill patients' delirium and related outcomes. Issue 1 (15th January 2019) - Papathanassoglou, Elizabeth D E; Skrobik, Yoanna; Hegadoren, Kathleen; Thompson, Patrica; Stelfox, Henry Thomas; Norris, Colleen; Rose, Louise; Bagshaw, Sean M; Meier, Michael; LoCicero, Cheryl; Ashmore, Rhonda; Sparrow Brulotte, Tiffany; et al.
Abstract : Introduction: Delirium is a common complication of critical illness, associated with negative patient outcomes. Preventive or therapeutic interventions are mostly ineffective. Although relaxation-inducing approaches may benefit critically ill patients, no well-designed studies target delirium prevention as a primary outcome. The objective of this study is to assess feasibility and treatment effect estimates of a multimodal integrative intervention incorporating relaxation, guided imagery and moderate pressure touch massage for prevention of critical illness delirium and for related outcomes. Methods and analysis: Randomised, controlled, single-blinded trial with two parallel groups (1:1 allocation: intervention and standard care) and stratified randomisation (age (18–64 years and ≥65 years) and presence of trauma) with blocking, involving 104 patients with Intensive Care Delirium Screening Checklist (ICDSC): 0–3 recruited from two academic intensive care units (ICUs). Intervention group participants receive the intervention in addition to standard care for up to five consecutive days (or until transfer/discharge); control group participants receive standard care and a sham intervention. We will assess predefined feasibility outcomes, that is, recruitment rates and protocol adherence. The primary clinical outcome is incidence of delirium (ICDSC ≥4). Secondary outcomes include pain scores, inflammatory biomarkers, heart rate variability, stress and quality of life (6 weeks and 4 months) post-ICU discharge. Feasibility measures will be analysed descriptively, and outcomes will be analysed longitudinally. Estimates of effects will be calculated. Ethics and dissemination: The study has received approval from the Human Research Ethics Board, University of Alberta. Results will inform the design of a future multicentre trial. Trial registration number: NCT02905812 ; Pre-results.